Study of Brand Equity in Terms of the Role of Integrated Marketing Communication, Perceived Quality, and Brand Awareness - Devi, Febrimelia; Nuvriasari, Audita (East Asian Journal of Multidisciplinary Research, 2024)
The aim of this research is to examine the impact of integrated marketing communications, perceived quality, and brand awareness on Scarlett skincare brand equity. This study includes a sample of 100 respondents who used Scarlett skincare. The sampling technique was determined by purposive sampling.  Data collection in this study was done using survey method, with a questionnaire as the research instrument. The data analysis was performed using multiple linear regression. This research produces that Integrated Marketing Communication, Perceived Quality and Brand awareness has a positive and significant impact on Scarlett skincare brand equity.